Feasibility trial of metformin XR in people with pre-diabetes and stroke (MIPPS)-randomised open blinded endpoint controlled trial. (April 2021) - Tabesh, Marjan; Hachem, Mariam; Lau, Lik-Hui; Borschmann, Karen; Churilov, Leonid; Price, Sarah A.L.; Sumithran, Priya; Donnan, Geoffrey; Zajac, Jeffrey; Thijs, Vincent; Ekinci, Elif I.
Highlights: Metformin XR is feasible and safe for people admitted with stroke and pre-diabetes. Metformin XR is well tolerated with no related side effects. Strategies are needed to improve adherence in future trials. Abstract: Aims: Pre-diabetes is a common condition that affects about 16.4% of Australian adults. Hyperglycaemia is a strong risk factor for the development of stroke. Metformin XR is an approved medication to treat type 2 diabetes in Australia but not pre-diabetes. Additionally, whether it is tolerated following a stroke is unclear. In this pilot study, we aimed to assess the feasibility of Metformin XR in people with stroke and pre-diabetes. Methods: In this PROBE design trial, people who had recent stroke (within 3 months) with pre-diabetes were randomized to either the active arm (n = 13) receiving usual care plus Metformin XR (500 mg daily increased to a total daily dose of 1500 mg) or the control group receiving only usual care (n = 13). At baseline & after four months of intervention, clinical and biomedical characteristics, cardiovascular risk factors and medication data were recorded. At one month and 2.5 months into the study, compliance rate and side effects were determined. Results: This trial showed that it is feasible to recruit, retain and monitor participants. However, the compliance rate was low. Adherence to metformin XR was 52% (IQR:42% to 61%) based on the remaining tablets in the container after 4 months of intervention. None of the reported side effects were deemed to be related to the study treatment and no significant differences were observed between the metformin XR and the control group. Conclusion: Treatment with Metformin XR in participants admitted with stroke and with pre-diabetes is feasible and safe. Strategies are needed to improve adherence in future trials.